Shift in HPAI infection dynamics causes significant losses in seabird populations across Great Britain. (7th October 2022) - Falchieri, Marco; Reid, Scott M.; Ross, Craig S.; James, Joe; Byrne, Alexander M. P.; Zamfir, Madalina; Brown, Ian H.; Banyard, Ashley C.; Tyler, Glen; Philip, Emma; Miles, Will
Abstract: This focus article has been prepared by Marco Falchieri, Scott M. Reid, Craig S. Ross, Joe James, Alexander M. P. Byrne, Madalina Zamfir, Ian H. Brown and Ashley C. Banyard of the APHA; Glen Tyler and Emma Philip of NatureScot; and Will Miles of Scottish Oceans Institute, School of Biology, University of St Andrews.